Leadership in Canadian Healthcare: Navigating Change Through Effective Governance - Renée Légaré; Ian Cullwick (Healthcare Management Forum, 2026)
This article examines the evolving internal governance dynamics of Canadian hospitals, with a focus on the triangular leadership relationship between the Board of Directors, Chief Executive Officer, and Chief of Staff. Drawing on research from seven eastern Ontario healthcare institutions, it identifies three distinct governance interaction models and highlights how, post-pandemic, there has been an accelerated shift toward more integrated, collaborative leadership. Key findings include persistent gaps in non-financial delegated authorities, sub-optimal Chief of Staff performance management, and succession planning, and reinforcing that trust and transparency between the Board Chair, Chief Executive Officer, and Chief of Staff remain the ultimate foundational pillars of governance effectiveness.